THEORETICAL ASPECTS OF SOCIAL MANAGEMENT AS RESEARCH OBJECT (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The paper is about the scientific category "social management". A number of derived theoretical and methodological problems regarding the essence of the category are formed. Differences between the interpretation of the general categories "management" and "managing" are given. Various definitions of the studied term are presented. The fact of terminological uncertainty and absence of a universal scientific approach to the interdisciplinary research object "social management" is noted, which is due to the polycomprehensiveness and certain uncertainty of the structural components. The author made an attempt to form a universal definition of the category "social management", which is based on a combination of two main aspects: management of social systems in combination with solving social problems. Various aspects of management of social systems (enterprises, organizations, collectives) and peculiarities of the researched category are presented. The general scientific principles and ideas formed by management classics: F. Taylor, H. Fayol, H. Emerson, are summarized. The role of the team as a kind of stabilizer in the process of enterprises and organizations functioning is analyzed, and various shortcomings in its evaluation are given. The fact of an integrated approach in forming methodological core, which synthesizes three interrelated paradigms: managerial, psychological, social and economic, is established. A number of specialized theories are singled out: the system theory of the firm, the theory of social action, and the theory of service state. Attention is focused on the methodology of the system theory of the firm, which is characterized by a certain fragmentation, different research subjects in the main areas: the processes of forming and implementing management decisions, the search for key factors of the firm's market success (strategic theory), concentration on the problems of the production sphere. A number of specific features of social management are given. It was concluded that modern management is primarily socially oriented.
Keywords: social management, management, managing, scientific theories, social contradictions